The cytosolic iron–sulfur cluster assembly (CIA) pathway is required for replication stress tolerance of cancer cells to Chk1 and ATR inhibitors - Abena B. Redwood (Nature Portfolio, 2021)
Abstract The relationship between ATR/Chk1 activity and replication stress, coupled with the development of potent and tolerable inhibitors of this pathway, has led to the clinical exploration of ATR and Chk1 inhibitors (ATRi/Chk1i) as anticancer therapies for single-agent or combinatorial application. The clinical efficacy of these therapies relies on the ability to ascertain which patient populations are most likely to benefit, so there is intense interest in identifying predictive biomarkers of response. To comprehensively evaluate the components that modulate cancer cell sensitivity to replication stress induced by Chk1i, we performed a synthetic-lethal drop-out screen in a cell line derived from a patient with triple-negative breast cancer (TNBC), using a pooled barcoded shRNA library targeting ~350 genes involved in DNA replication, DNA damage repair, and cycle progression. In addition, we sought to compare the relative requirement of these genes when DNA fidelity is challenged by clinically relevant anticancer breast cancer drugs, including cisplatin and PARP1/2 inhibitors, that have different mechanisms of action. This global comparison is critical for understanding not only which agents should be used together for combinatorial therapies in breast cancer patients, but also the genetic context in which these therapies will be most effective, and when a single-agent therapy will be sufficient to provide maximum therapeutic benefit to the patient. We identified unique potentiators of response to ATRi/Chk1i and describe a new role for components of the cytosolic iron–sulfur assembly (CIA) pathway, MMS19 and CIA2B-FAM96B, in replication stress tolerance of TNBC.